Iustin Ilianovich Janelidze - Nushtaev, I. (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The authors generalize the main landmarks in the life of an outstanding scientist, teacher, organizer, field surgeon, Lieutenant General of Medical Service, one of the first full members of the Academy of Medical Sciences of the USSR Iustin Ilianovich Janelidze and acquaint readers with his works.